Improvement of human keratinocyte migration by a redox active bioelectric dressing. - Jaideep Banerjee; Piya Das Ghatak; Sashwati Roy; Savita Khanna; Emily K Sequin; Karen Bellman; Bryan C Dickinson; Prerna Suri; Vish V Subramaniam; Christopher J Chang; Chandan K Sen (PLoS ONE)
Exogenous application of an electric field can direct cell migration and improve wound healing; however clinical application of the therapy remains elusive due to lack of a suitable device and hence, limitations in understanding the molecular mechanisms. Here we report on a novel FDA approved redox-active Ag/Zn bioelectric dressing (BED) which generates electric fields. To develop a mechanistic understanding of how the BED may potentially influence wound re-epithelialization, we direct emphasis on understanding the influence of BED on human keratinocyte cell migration. Mapping of the electrical field generated by BED led to the observation that BED increases keratinocyte migration by three mechanisms: (i) generating hydrogen peroxide, known to be a potent driver of redox signaling, (ii) phosphorylation of redox-sensitive IGF1R directly implicated in cell migration, and (iii) reduction of protein thiols and increase in integrinαv expression, both of which are known to be drivers of cell migration. BED also increased keratinocyte mitochondrial membrane potential consistent with its ability to fuel an energy demanding migration process. Electric fields generated by a Ag/Zn BED can cross-talk with keratinocytes via redox-dependent processes improving keratinocyte migration, a critical event in wound re-epithelialization.